Public health approach to address maternal mortality - Sanjay K Rai; K Anand; Puneet Misra; Shashi Kant; Ravi Prakash Upadhyay (Indian Journal of Public Health, 2012)
Reducing maternal mortality is one of the major challenges to health systems worldwide, more so in developing countries that account for nearly 99% of these maternal deaths. Lack of a standard method for reporting of maternal death poses a major hurdle in making global comparisons. Currently much of the focus is on documenting the "number" of maternal deaths and delineating the "medical causes" behind these deaths. There is a need to acknowledge the social correlates of maternal deaths as well. Investigating and in-depth understanding of each maternal death can provide indications on practical ways of addressing the problem. Death of a mother has serious implications for the child as well as other family members and to prevent the same, a comprehensive approach is required. This could include providing essential maternal care, early management of complications and good quality intrapartum care through the involvement of skilled birth attendants. Ensuring the availability, affordability, and accessibility of quality maternal health services, including emergency obstetric care (EmOC) would prove pivotal in reducing the maternal deaths. To increase perceived seriousness of the community regarding maternal health, a well-structured awareness campaign is needed with importance be given to avoid adolescent pregnancy as well. Initiatives like Janani Surakhsha Yojna (JSY) that have the potential to improve maternal health needs to be strengthened. Quality assessments should form an essential part of all services that are directed toward improving maternal health. Further, emphasis needs to be given on research by involving multiple allied partners, with the aim to develop a prioritized, coordinated, and innovative research agenda for women′s health.